All the lonely people: Loneliness in Australia, 2001-2009 - Baker, D (The Australia Institute, 2012)
Loneliness is the disconnect felt between desired interpersonal relationships and those that one perceives they currently have. While the subjective nature of this experience makes measuring loneliness difficult, understanding loneliness is important for the development of a range of social policies. The availability of longitudinal Household Income and Labour Dynamics in Australia (HILDA) Survey data now makes it possible to track loneliness in Australia over the past decade. This paper studies the long-term pattern of loneliness and identifies demographic characteristics and risk indicators associated with this experience and finds the incidence of loneliness in Australia is growing. The use of online social networking sites and how this may influence the experience and prevalence of loneliness is also explored.
Institute Paper No.9
Keywords: Relationships; Satisfaction; Health -- Wellbeing; Health and wellbeing; Health; Satisfaction; Relationships; Wellbeing; Health and wellbeing